OBSTRUCTIVE SLEEP APNEA AND ITS MANAGEMENT - DR. M.P.SANTHOSH KUMAR (International Journal of Pharma and Bio Sciences, 2015)
Obstructive sleep apnea [OSA] is a potentially serious disorder affecting millions of people around the world. Many of these individuals are undiagnosed while those who are diagnosed are not compliant with any single treatment. Behavior modifications, continuous positive airway pressure, oral appliances are the non surgical modalities of treatment. Surgical procedures like uvulopalatopharyngoplasty, maxillomandibular advancement surgery are done in the management of OSA. This review article discusses about the etiology, pathophysiology, predisposing factors, clinical features, diagnosis of OSA and also about the various treatment modalities for OSA.